IMPLEMENTASI PEMBELAJARAN IPS MODEL PROJECT BASED LEARNING DENGAN MEDIA VIRTUAL CANDI SUKUH UNTUK MENINGKATKAN KESADARAN SEJARAH SISWA KELAS VII SMP IT MTA KARANGANYAR TAHUN AJARAN 2019/2020 - Siti Samsiyah; Akhmad Arif Musadad; Musa Pelu (CV Sintesia, 2023)
This study aims to: (1) Increase the historical awareness of class VII D students of SMP IT MTA Karanganyar even semester of the 2019/2020 academic year through the implementation of Social Studies learning model Project Based Learning with virtual media of Sukuh temple. This research is a Classroom Action Research (CAR) with 2 cycles. Cycle 1 was carried out on June 15, 2020 and Cycle 2 was carried out on June 22, 2020. The research subjects were Class VII D students of SMP IT MTA Karanganyar, totaling 32 students. The data collection techniques used were test and non-test. The research instruments were historical awareness questionnaires. Data analysis was carried out by qualitative analysis and quantitative analysis.The results showed that the implementation of social studies learning model project based learning with virtual media of Sukuh temple can increase historical awareness of class VII D students of SMP IT MTA Karanganyar even semester of the 2019/2020 academic year. The mean historical awareness set from school was 70 (75%). After being given the action for two cycles, the average result of historical awareness in pre-cycle 39 (low) or 66% (21) of low history awareness students, cycle 1 increased to 60 (moderate) or 28% (9) of high historical awareness students and 72 % (23) students of moderate historical awareness, cycle 2 increased again to 73 or 66% (21) students of historical awareness were high, 25% (8) of students had very high historical awareness. This achievement has exceeded the target set, which is an average of 70 or 75%. The increase in historical awareness from cycle 1 to cycle 2 was 22% and from pre-cycle to cycle 1 was 54%. The findings of this study are that the implementation of social studies learning model project based learning with virtual media of Sukuh temple can increase historical awareness of class VII D students of SMP IT MTA Karanganyar in the 2019/2020 academic year.